Effect of the visible light irradiation of fullerene containing composites on the ros generation and the viability of tumor cells - Ritter, U.; Scharff, P.; Prylutska, S.V.; Matyshevska, O.P.; Burlaka, A.P.; Golub, A.А.; Potebnya br, G.P.; Prylutskyy, Y.I. (Experimental Oncology, 2006)
Aim: To study the effect of fullerene-containing composites, irradiated by visible light, on the radical oxygen species (ROS) generation in thymocytes, ascitic cells from Erlich’s tumor and leukemia cells L1210; to investigate viability of these cells in the presence of fullerene-containing composites under irradiation conditions. Materials and Methods: The viability of cells was evaluated by staining with 0.4% solution of the trypan blue; ROS were detected with the use of electron paramagnetic resonance (EPR) spectroscopy and spin traps; solutions of fullerene-containing composites were irradiated with mercury-vapor lamp. Results: We demonstrated that under irradiation conditions fullerene-containing composites increase the rate of ROS generation and decrease the number of viable tumor cells. Conclusions: The obtained data allow to consider the fullerene-containing composites as potential agents for photodynamic therapy. Цель: изучить влияние фуллеренсодержащих композитов, облученных видимым светом, на генерирование радикальных форм кислорода (РФК) в клетках тимоцитов, асцитного рака Эрлиха и лейкоза L1210. Исследовать жизнеспособность этих клеток в присутствии облученных фуллеренсодержащих композитов. Методы: жизнеспособность клеток определяли с использованием 0,4 % раствора трипанового синего; РФК регистрировали методом ЭПР- спектроскопии и спиновых ловушек; облучение водных раcтворов фуллеренсодержащих композитов в видимом диапазоне осуществляли с помощью ртутной лампы. Результаты: показано, что фуллеренсодержащие композиты при облучении повышают скорость генерирования РФК и уменьшают количество жизнеспособных опухолевых клеток. Выводы: полученные результаты позволяют рассматривать фуллеренсодержащие композиты как потенциальные препараты для фотодинамической терапии.